Examining the reformist thoughts of al- Tāhir ibn ‘Āshūr - Suleiman, Hassan; Alwi, Alwi; Busari, Saheed Abdullahi (Universiti Sains Islam Malaysia (USIM), 2024)
Al-Sheikh Muḥammad al-Tāhir ibn ‘Āshūr, who lived between 1296 AH (1879 AD) and 1393 AH (1973 AD), is considered one of the eminent intellectuals of the modern era and an influential figure among the generation of writers and scholars. He is described as the pioneer of Maqasid thought in contemporary jurisprudence and has developed in this regard the book Maqāṣid al-Sharī‘ah al-Islāmiyyah (The Objectives of the Islamic Shariah), as well as his famous book of Quranic exegesis al-Taḥrīr wa al-Tanwīr. To this effect, this study identifies the reformist features of al-Tāhir ibn ‘Āshūr in his books and writings that brought about a renaissance in various branches of knowledge such as Shariah, tafsīr, and education. A review of the literature suggests that al-Tāhir ibn ‘Āshūr’s reformist ideas have not received sufficient academic attention. Therefore, the study raised some questions, including: Who is Tāhir ibn ‘Āshūr? What were Tāhir ibn ‘Āshūr’s reformist viewpoints, and how did he propagate them out, most particularly in education? The study follows the descriptive approach to trace Ibn ‘Āshūr’s biography as well as the analytical approach in discussing the thought of al-Tāhir ibn ‘Āshūr on the scientific and educational level. The study concludes that Muḥammad al-Ṭāhir ibn ‘Āshūr (may Allah have mercy on him) is one of the eminent intellectuals in the Islamic world, whose innovative views and great writings came as a revolution against tradition and inertia and a revolution against intellectual inaction and civilizational stagnation.